Bare Lives in the Shadow of Empires: Jesus, Comfort Women, and Theology of Resistance - Lim, Sung Uk (Theology today, 2018)
This article delves into the biopolitical dimension of Jesus and Korean comfort women by engaging with the insight yet to be gleaned from Giorgio Agamben's notion of bare life. Seen through this biopolitical prism, Jesus in the passion narratives of the Gospels can be understood as a paradigmatic bare life in his sheer ambiguity, which swings back and forth between terrestrial and celestial dominions. Similarly, Korean comfort women, albeit in a different historical and sociocultural context, can also be viewed as bare lives under ruthless Japanese colonial rule (1910-1945). My contention here is that, through the process of theological thinking, the reconfiguration of Jesus as a subversive bare life offers fresh insight into the agency of Korean comfort women in the sense that their bare lives have so far resisted the unjust world in their search of human rights and dignity. In spite of his tribulations between the Jewish and Roman authorities, Jesus unsettles these sovereign powers in such an ambiguous space. In a similar fashion, Korean comfort women have broadcast the atrocious brutality of Japanese colonial rule in the ambiguous zone beyond the juridical realms-Korean, Japanese, or otherwise-at the national and international levels. The foremost point to remember is that a commemoration of Jesus' life as the most paradigmatic example of bare life can inspire Korean comfort women to deal with their agony in assuming bare life in the unswerving hope of justice yet to be served through divine intervention in the terrestrial sovereignty in liminal space and time.